Effects of global and local ply-reinforcements of critical components on crush performances of 2D tri-axially braided CFRP J-shaped fuselage frame. Issue 3 (4th May 2022) - Liu, Xiaochuan; Jiang, Hongyong; Ren, Yiru; Xi, Xulong
Abstract: With the development of aircraft industry, there is an urgent demand for pursuing higher crashworthiness design standard of fuselage. However, there is a challenge for improving the crush performances of fuselage with low design and fabrication cost. To explore optimal design areas, effects of global and local ply-reinforcements of critical components on crush performances of 2D tri-axially braided CFRP J-shaped fuselage frame are predicted with validated continuum damage model. The finite element model composed of three critical components (e.g. outer flange, web, and inner flange) can accurately predict the experimental maximum failure load and breakage mode. Then, the crush behaviours of fuselage frame with global and local ply-reinforcements are respectively compared among three parts. It is found that local ply-reinforcements slightly increase structural stiffness, failure load, and SEA but global ply-reinforcements present greater improvements, especially for the outer flange and web. Further, effects of ply number of each part on crush behaviours of fuselage frame are predicted. Results show that increasing ply number presents higher performances but the SEA only increases for global ply-reinforcement of outer flange. It is concluded that globally reinforcing the outer flange has the highest reinforcement efficiency with a low increase of weight. This study provides a preferential reinforcement design idea for the fuselage to keep the light-weight and high-strength.